The influence of enterosorption on some haematological and biochemical indices of the normal rats after single injection of melphalan - Shevchuk, O.O.; Posokhova, К.А.; Sidorenko, A.S.; Bardakhivska, К.І.; Maslenny, V.M.; Yushko, L.A.; Chekhun, V.F.; Nikolaev, V.G. (Experimental Oncology, 2014)
Aim: One of the most prominent side effects of intensive cancer chemotherapy is bone marrow suppression which is an independent negative prognostic factor for the time to tumor progression. The aim of the study was to evaluate the myeloprotective possibilities of carbon enterosorbents in the case of usage of alkilating drug melphalan (L-PAM). Materials and Methods: L-PAM was injected intravenously to healthy inbred rats to cause the myelosuppression. 3 days before and 7 days after this, suspension of two types of carbon granulated enterosorbents were administered per os one time per day. On 8th day after L-PAM injection, the rats were weighted and blood and liver tissue were taken under Ketamine general anesthesia for biochemical examination. Peripheral blood smears were made also. Results: Melphalan at a dose of 3 mg/kg causes expressed myelotoxic reaction: leucopenia, decreasing of erythrocytes, hemoglobin and platelets counts. Even on 8th day after single injection of this cytostatic we can detect expressed signs of oxidative stress like increasing of hydroperoxides, TBA-reactive substances, and decreasing of activity and level of main endogenic antioxidants — superoxide dismutase (SOD), catalase and reduced glutathione. L-PAM causes also the violation of kidney function such as increase of urea and creatinine level; and rising of endogenic intoxication with elevation of middle mass molecules level. In a dose of 3 mg/kg melphalan has no negative influence on liver function on 8th day of experiment. Enterosorption with carbon enterosorbents C1 (bulk density γ = 0.28 g/cm³, granules diameter 0.15–0.25 mm, BET pore surface 1719 m²/g, therapeutic dosage 1400 mg/kg) and C2 (bulk density γ = 0.18 g/cm³, granules diameter 0.15–0.25 mm, BET pore surface 2162 m²/g, therapeutic dosage 900 mg/kg) diminishes and mitigates negative side effects caused by single intravenous injection of melphalan. Carbon enterosorbent C2 have rather more expressed positive effect than C1 for practically all indices. The most important curative effect due to C2 administration is prominent myeloprotection of bone marrow of experimental animals. Conclusion: Carbon enterosorbent C2 is promising and perspective sorbent for prophylaxis and treatment of side effects of cytostatic chemotherapy including myelotoxicity, mucositis, kidney injuries, gonadotoxicity, etc. Key Words: L-PAM, myelosuppression, oxidative stress, carbon enterosorbents.